Creative Thinking and the Use of Imagination as Survival Skills - Gilmor, Jane (2019)
At a time when immigration policies dem- onstrate increasing intolerance and social injustice we, as artists concerned with so- cial issues, wanted to demonstrate that the visual arts, in particular, and culture, in a broader sense, are an important means for embracing diference. None of us can be sure - whether short-term or long-term, as refugees from war, natural disaster, or other causes - that we might not be in a similar situation, without our home or country, being shuled between temporary living spaces. Searching for a better future in a new place is something common to all liv- ing species, and we, as intelligent beings living in civilized societies, must provide new forms of welcoming and inclusion that incorporate the arts and encourage creative thinking and the use of imagi- nation as survival strategies. hrough the Shifting Ground project, sponsored by he Iowa Ceramic Center and Glass Workshop (ICCGS), we hoped to empower and give visibility to undervalued immigrant groups in our own community, while also promot- ing social and cultural sustainability.